Collaborative learning and individual work performance in coworking spaces - Oswald, Kolja; Zhao, Xiaokang (Journal of Business Economics and Management, 2022)
Coworking spaces are becoming increasingly popular. Throughout literature, coworking spaces are commonly known as collaborative environments. Yet, there is a lack of research on the mechanisms of the collaborative practices within coworking spaces. This research identifies collaborative learning as a major collaborative practice within coworking spaces, and develops a conceptual framework including two other variables: individual motivation to learn and individual work performance. Exploratory factor analysis to establish the reliability and validity of this framework. Next, a survey study was conducted of 169 coworking space members and PLS-SEM was used to do a factor analysis and evaluate the structural model created. It is found that individual motivation to learn positively impacts collaborative learning, collaborative learning positively impacts individual work performance, and that collaborative learning acts as a full mediator between individual motivation to learn and individual work performance. These findings demonstrate how collaborative learning can be key in improving individual work performance in coworking spaces. Furthermore, these findings position collaborative learning as a theory that deserves further attention in coworking space research. These findings also suggest that coworking space operators may want to further encourage collaboration and incentivize learning in their space. First published online 14 December 2021